2019
DOI: 10.1038/s41467-019-09820-8
|View full text |Cite
|
Sign up to set email alerts
|

Nodal rings and drumhead surface states in phononic crystals

Abstract: Three-dimensional topological nodal lines, the touching curves of two bands in momentum space, which give rise to drumhead surface states, provide an opportunity to explore a variety of exotic phenomena. However, solid evidence for a flat drumhead surface state remains elusive. In this paper, we report a realization of three-dimensional nodal line dispersions and drumhead surface states in phononic crystal. Profiting from its macroscopic nature, the phononic crystal permits a flexible and accurate fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 33 publications
0
59
0
1
Order By: Relevance
“…Instead of the Hamiltonian, it is the Laplacian J that determines the steady state behavior of a circuit via I = JV, where I and V are the input currents and potentials at all the nodes. Since the circuit engineering of desired Laplacian is a mature topic [48,49,68,69] with Hermitian nodal drumhead states even experimentally measured [46,70,71], we shall relegate its details to the Supplement [55]. As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of the Hamiltonian, it is the Laplacian J that determines the steady state behavior of a circuit via I = JV, where I and V are the input currents and potentials at all the nodes. Since the circuit engineering of desired Laplacian is a mature topic [48,49,68,69] with Hermitian nodal drumhead states even experimentally measured [46,70,71], we shall relegate its details to the Supplement [55]. As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As it turns out, Weyl points are only one member of a broader family of topologically nontrivial band degeneracies. Researchers have demonstrated photonic/acoustic crystals with topological nodal lines—band degeneracies lying along one-dimensional (1D) curves in momentum space—which are associated with Berry phase winding of π and drumhead surface states 2326 . Recent theoretical studies have also revealed the possibility of higher-dimensional topological band degeneracies, such as twofold two-dimensional (2D) nodal surfaces 2734 .…”
Section: Introductionmentioning
confidence: 99%
“…Note that a very recent work by S. Zhang et al has made the first step toward the experimental study of 3D Dirac points in classical wave systems28 .Interestingly, the Dirac points are constructed by electromagnetic duality symmetry (which are unique in electromagnetic systems), also strikingly different from the crystalline symmetry involved here. Starting with our structure, one can design 10 various interesting 3D acoustic topological states (e.g., Weyl points29,31 and line nodes37,38 ) through symmetry reduction. Here we would like to mention that, more or less, there is dissipation loss in our airborne phononic crystal, which may introduce a non-Hermitian modification in the effective Hamiltonian.…”
mentioning
confidence: 99%